Genus Begoniaceae: A Review of Phytochemical and Pharmacological Activity: Genus Begoniaceae: Kajian Review Fitokimia dan Aktivitas Farmakologis - Ayunanda, Nurul Putri Ramadhani; Fitriani, Hannie; Syukri, Yandi; Zubair, Muhammad Sulaiman (Universitas Tadulako, 2025)
Background: Begonia sp. (Begoniaceae) contains phytochemical compounds that possess significant pharmacological activities such as antioxidants, antibacterials, anticancer agents, and even immunostimulants. Objective: Provide information about the phytochemical compounds and pharmacological activities of Begonia species. Methods: This narrative review was conducted by searching the literature using journal databases such as Google Scholar, PubMed, and ScienceDirect relevant from 2014 to 2024. Results: Based on review of various literature studies, 19 articles were found that met the inclusion and exclusion criteria of this research. The literature obtained explains that Begonia sp. has been proven to possess various pharmacological activities influenced by phytochemical compounds. Conclusions: Phytochemical compounds in Begonia species can support research and present opportunities in drug development.